Curriculum Innovation Program Fellowship "Serving the Community Through Service Learning" - Jackson, Shirley A. (2011)
Dr. Jackson worked on her Curriculum Innovation Program fellowship, "Serving the community through service learning," completed write-up for Ethnic Studies Curriculum-Related Activity Grant for "Ethnic Studies Program Development at Southern Connecticut State University," worked on several articles and two book proposals encompassing research of race issues and their representation in contemporary cartoons, as well as attended conferences, both as a presenter and a chair, participated in workshops, and reviewed textbook chapters and an article.
Keywords: SCSU; Sabbatical leave report; dept.soc; faculty_collection; sabbatical_report

The Loveless Family: Getting Past Estrangement and Learning How to Love - Bloch, Jon P. (Praeger, 2011)
This scholarly and personal exploration of what it is like to grow up feeling unloved describes personality types and syndromes that often manifest, regardless of whether the family unit was "dysfunctional" or not., This scholarly and personal exploration of what it is like to grow up feeling unloved describes personality types and syndromes that often manifest, regardless of whether the family unit was ""dysfunctional"" or not.
Keywords: Families; Psychological aspects; Parenting; Dysfunctional families; Adult children of dysfunctional families; Love; dept.soc; faculty_collection